Distinguishing Atherosclerotic Calcifications in Dry Bone: Implications for Forensic Identification. Issue 3 (31st October 2018) - Biehler‐Gomez, Lucie; Maderna, Emanuela; Brescia, Gloria; Caruso, Valentina; Rizzi, Agostino; Cattaneo, Cristina
Abstract: Atherosclerotic calcifications, as calcified atheromatous elements, are markers of cardiovascular disease. However, the literature gives little information regarding their morphological aspect, making their identification very rare in skeletonized cases. In this paper, we document the morphological, histological, and SEM aspects of atherosclerotic plaques collected from unclaimed cemeterial skeletal remains from an identified osteological collection and extracted from well‐preserved cadavers autopsied at the medico‐legal institute of Milan. Each of the three analyses provided similar results: atherosclerotic calcifications are convex‐concave plaques with a stratified structure, a pale‐yellow coloration in autopsy cases and yellow to brown when recovered in dry bone. Histologically, undecalcified and decalcified sections showed a stratified aspect formed by superimposed layers. Lastly, the SEM analysis showed a precise view of the stratified structure of the plaques in transverse section. As markers of disease, atherosclerotic calcifications can provide important antemortem information on the deceased that may be compared to antemortem data.